Maritime Cyber Security Analysis – How to Reduce Threats? - Mraković, Ivan; Vojinović, Ranko (Transactions on Maritime Science, 2019)
Maritime cyber security management requires a holistic approach as there is an increase in complexity, digitalization, and automation of systems in maritime industry. Numerous interconnected systems between ship and shore, which are in need of a special focus in the internet environment, are increasing on daily basis. Nowadays one of the major concerns in maritime computing is vulnerability to cyber-attacks. In maritime industry, cyber incidents can lead to loss of life, loss of control over ships or sensitive data, as well as ship and/or cargo hijacking. This paper therefore covers key problems of maritime industry from cyber security perspective and proposes solutions on how to eliminate or minimize them.